Expansion and improved permeability of post-secondary education in Germany : consequences for social inequalities in educational attainment - Tieben, Nicole [Verfasser]; Rohrbach-Schmidt, Daniela [Verfasser] (My University, 2021)
„With this contribution, we examine the role of non-linear pathways to a higher education degree for social inequality in educational attainment. Unlike previous research, we compared the initial and final distributions of higher education degree attainment rather than the attainment of a higher education entrance certificate using the unconditional approach. Moreover, we calculated the attainment gap between social background groups (expressed as difference of predicted probabilities) rather than differences in transition rates (expressed as odds ratios). Our results show that higher education in Germany has expanded through direct and indirect transitions likewise. An increasing share of the students who did not enter higher education directly use the improved permeability between vocational and higher education to enter higher education via indirect pathways. Across cohorts, the absolute chances of obtaining a higher education degree hence have increased across all socio-economic groups and all groups increased their participation via indirect pathways. However, we also observe that the attainment gap between the low/middle socio-economic background group and the high background group has not substantially declined across cohorts and that in all cohorts the higher socio-economic background groups maintain their advantage over the lower groups. Our results furthermore suggest that improved permeability does not contribute to decreasing inequality of higher education degree attainment.“ (authors’ abstract; BIBB-Doku)
Keywords: S 1.4 Hochschulbildung; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; 370; 300; Hochschulsystem; Durchlässigkeit im Bildungssystem; Nicht traditionell Studierender; Hochschulabsolvent; Studienerfolg; Bildungschance; Soziale Ungleichheit